Research Hotspots and Trends of Peripheral Nerve Injuries Based on Web of Science From 2017 to 2021: A Bibliometric Analysis - Zhang, Shiwen; Huang, Meiling; Zhi, Jincao; Wu, Shanhong; Wang, Yan; Pei, Fei (Frontiers in Neurology, 2022)
BACKGROUND: Peripheral nerve injury (PNI) is very common in clinical practice, which often reduces the quality of life of patients and imposes a serious medical burden on society. However, to date, there have been no bibliometric analyses of the PNI field from 2017 to 2021. This study aimed to provide a comprehensive overview of the current state of research and frontier trends in the field of PNI research from a bibliometric perspective. METHODS: Articles and reviews on PNI from 2017 to 2021 were extracted from the Web of Science database. An online bibliometric platform, CiteSpace, and VOSviewer software were used to generate viewable views and perform co-occurrence analysis, co-citation analysis, and burst analysis. The quantitative indicators such as the number of publications, citation frequency, h-index, and impact factor of journals were analyzed by using the functions of "Create Citation Report" and "Journal Citation Reports" in Web of Science Database and Excel software. RESULTS: A total of 4993 papers was identified. The number of annual publications in the field remained high, with an average of more than 998 publications per year. The number of citations increased year by year, with a high number of 22,272 citations in 2021. The United States and China had significant influence in the field. Johns Hopkins University, USA had a leading position in this field.JESSEN KR and JOURNAL OF NEUROSCIENCE were the most influential authors and journals in the field, respectively. Meanwhile, it was recommended to focus on the important roles of Schwann cell, a three-dimensional hierarchically aligned fibrin nanofiber hydrogel, brief electric stimulation, dorsal root ganglion, mesenchymal stem cell, and satellite glial cells in reducing pain after nerve injury, controlling inflammation to prevent secondary injury, and promoting post-injury regeneration, which is not only hot topics now but is also forecast to be of continued focus in the future. CONCLUSION: This is the first study to conduct a comprehensive bibliometric analysis of publications related to PNI from 2017 to 2021, whose bibliometric results can provide a reliable source for researchers to quickly understand key information in this field and identify potential research frontiers and hot directions.